Multicultural Islamic Education: Reconstructing the Curriculum and Implementation Strategies in the Era of Digital Polarization - Diantoro Diantoro; Rustam Ibrahim (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Multicultural Islamic education represents an educational paradigm that integrates the normative values of Islam with the essential recognition of cultural, ethnic, and social diversity within society (Zulkarnain et al., 2026; Mashuri et al., 2025). In the sociological context of Indonesia’s pluralistic society, this approach serves as a strategic instrument for fostering students’ character development toward tolerance, moderation, and inclusivity (Takunas et al., 2024; Subhi, 2022). Using a library research method combined with content analysis of recent scholarly literature (Snyder, 2019; Zed, 2014), the findings reveal that multicultural Islamic education extends beyond the mere transmission of religious doctrines; it plays a crucial role as an agent for cultivating harmonious national character (Fahri & Zainuri, 2023; Zulkarnain et al., 2026). Therefore, the effective implementation of this educational approach requires a comprehensive and systemic integration, including the reconstruction of an inclusivity-oriented curriculum, the strengthening of teachers’ pedagogical role modeling as agents of religious moderation, institutional policy support, and the creation of a school ecosystem that promotes universal humanitarian values (Mashuri et al., 2025; Takunas et al., 2024).